2013
DOI: 10.1002/stem.1343
|View full text |Cite
|
Sign up to set email alerts
|

Lin28a Regulates Germ Cell Pool Size and Fertility

Abstract: Overexpression of LIN28A is associated with human germ cell tumors and promotes primordial germ cell (PGC) development from embryonic stem cells in vitro and in chimeric mice. Knockdown of Lin28a inhibits PGC development in vitro, but how constitutional Lin28a deficiency affects the mammalian reproductive system in vivo remains unknown. Here, we generated Lin28a knockout (KO) mice and found that Lin28a deficiency compromises the size of the germ cell pool in both males and females by affecting PGC proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 20 publications
2
47
1
Order By: Relevance
“…Previously, we and others have shown that LIN28 plays an important role in germ cell development (West et al 2009;Shinoda et al 2013a) and is associated with human germ cell tumors (Gillis et al 2011;Murray et al 2013). Thus, we endeavored to overexpress Lin28 in PGCs by crossing mice containing a Lox-stop-Lox-Lin28a cassette (LSL-Lin28a) (Supplemental Fig.…”
Section: Lin28 Overexpression During Embryonic Kidney Development Leamentioning
confidence: 94%
“…Previously, we and others have shown that LIN28 plays an important role in germ cell development (West et al 2009;Shinoda et al 2013a) and is associated with human germ cell tumors (Gillis et al 2011;Murray et al 2013). Thus, we endeavored to overexpress Lin28 in PGCs by crossing mice containing a Lox-stop-Lox-Lin28a cassette (LSL-Lin28a) (Supplemental Fig.…”
Section: Lin28 Overexpression During Embryonic Kidney Development Leamentioning
confidence: 94%
“…This was confirmed by examining inducible let-7 transgenic mice, which overexpress let-7 miRNA (Shinoda et al 2013). Thus, expression of lin28 in the early ovary is critical for the down-regulation of miRNA let-7, which allows for the proliferation of PGCs necessary for normal adult ovarian function (Shinoda et al 2013). To determine if lin28 was equally important in growing oocytes and/or early embryonic development, a transgenic RNAi mouse was generated in which lin28a and lin28b were selectively knockeddown in growing oocytes (Flemr et al 2014).…”
Section: Mirna In Ovarian Developmentmentioning
confidence: 81%
“…Because let-7 miRNA are downstream targets of lin28, it was theorized that overexpression of let-7 would mimic loss of lin28. This was confirmed by examining inducible let-7 transgenic mice, which overexpress let-7 miRNA (Shinoda et al 2013). Thus, expression of lin28 in the early ovary is critical for the down-regulation of miRNA let-7, which allows for the proliferation of PGCs necessary for normal adult ovarian function (Shinoda et al 2013).…”
Section: Mirna In Ovarian Developmentmentioning
confidence: 87%
See 2 more Smart Citations